Training on Optimizing Digital Marketing to Improve Marketing for Micro, Small, and Medium Enterprises (MSMEs) in Mantrijeron District, Yogyakarta - Tarso, Dimas (Jurnal Pengabdian Masyarakat Bestari, 2024)
The training activity aimed to provide knowledge and skills on implementing digital marketing. Conducted on Saturday, September 7, 2024, in Mantrijeron District, the training included 40 participants consisting of local MSME actors. The event utilized a combination of lectures and hands-on practice. It began with an opening and introduction to digital marketing, followed by a presentation on the concept of digital marketing, discussions on common challenges faced by MSMEs, explanations of foreign terms related to digital marketing, and concluded with a practical session. As a result, participants acquired valuable insights into digital marketing, and many expressed a desire for assistance with business capital to support their growth in the region.